Preparation of high-strength waste-derived eco-friendly ceramic foam as face brick and its estimation of building energy consumption for thermal insulation - Sarkar T.; Naskar M.K.; Chakraborty A.; Roy P.K.; Chakraborty S. (My University, 2025)
Waste-derived ceramic foams as a logical solution for the reutilization of industrial solid wastes have been prepared using red mud and fly ash, eggshell as a foaming agent, and di-sodium tetraborate as a glass former. The effect of foaming (1–5 wt %) and glass-forming (20 wt %) agents on the microstructure, physico-mechanical properties, and chemical stability of foams are investigated. The optimized product (RFE3) with a total porosity (33%) and bulk density (2.14 g/cc) reveals high compressive strength (109.75 MPa) and low thermal conductivity (0.93 W/m•K) that is suitable as a load bearing outside building block face brick. The theoretical building energy simulation model using heat balance (HBM) and cooling load temperature difference (CLTD) method has revealed that the average annual energy conservation in India is 21816 MJ. Compared with the traditional face brick, our developed high strength ceramic foam face brick with low thermal conductivity saves satisfactory building energy consumption. The present work is relevant to international research regarding environment friendly building envelope construction. © 2024 Elsevier Ltd